Hypoxia-Inducible Factors as an Alternative Source of Treatment Strategy for Cancer. (14th August 2019) - Akanji, Musbau Adewumi; Rotimi, Damilare; Adeyemi, Oluyomi Stephen
Abstract : Hypoxia-inducible factors (HIFs) are transcription factors that activate the transcription of genes necessary to circumvent to hypoxic (low oxygen level) environments. In carcinogenesis, HIFs play a critical role. Indeed, HIF-1 α has been validated as a promising target for novel cancer therapeutics, even as clinical investigations have linked increased levels of HIF-1 α with aggressive cancer progression as well as poor patient prognosis. More so, inhibiting HIF-1 activity restricted cancer progression. Therefore, HIF-1 is a viable target for cancer therapy. This may be expected considering the fact that cancer cells are known to be hypoxic. In order to survive the hypoxic microenvironment, cancer cells activate several biochemical pathways via the HIF-1 α . Additionally, cellular and molecular insights have proved prospects of the HIF-1 α pathway for the development of novel anticancer treatment strategies. The biochemical importance of hypoxia-inducible factors (HIFs) cannot be overemphasized as carcinogenesis, cancer progression, and HIFs are intricately linked. Therefore, this review highlights the significance of these linkages and also the prospects of HIFs as an alternative source of cancer therapies.